ANALISIS DAMPAK PENERAPAN TEKNOLOGI BAGI MASYARAKAT DI MASA PANDEMI COVID-19 - Kadek Ayu Ariningsih; I Gusti Ngurah Made Desnanjaya; Putu Wirayudi Aditama; Tantri Pramawati (Politeknik Negeri Sriwijaya, 2021)
Corona Virus or Covid-19 is still a threat to society. This virus spreads very quickly through droplets or liquid droplets from coughing and sneezing, personal contact such as shaking hands, and touching objects or surfaces with the virus on them, then touching the mouth, nose, or eyes before washing hands. From observations made in the community, people need handwashing tools and automatic hand sanitizer to avoid direct contact with objects' surfaces. Technology in the form of Automatic Hand Sanitizer Using Ultrasonic Sensor and Arduino as hand sanitizer from bacteria without touching the hand sanitizer bottle that can be used and utilized by the public. This tool is implemented in Lodtunduh Village on Gianyar Regency, placed in one of the residents' houses Mr. Wayan Adhe Suwetha. This Automatic Hand Sanitizer technology makes it possible to work without any touch or pressure on objects, which will reduce the spread of viruses from objects that are often used to maximize the application of health protocols for the community, especially for Lodtunduh Gianyar community. The research was conducted using a descriptive qualitative method with data obtained through observation and sampling of the population regarding the impact of using the Automatic Hand Sanitizer technology.